A rare presentation of Susac syndrome: Report of three pediatric cases - Yalçınkaya, Beyza Çitçi; Ertürk Çetin, Özdem; Kılıç, Hüseyin; Demirci, Onat; Çokyaman, Turgay; Uygunoğlu, Uğur (Multiple sclerosis and related disorders, 2021)
Susac syndrome is a rare disorder that is clinically characterized by encephalopathy, retinopathy and hearing loss. Most of the reported cases in the literature are adult patients, pediatric presentation is extremely rare. Here we present three pediatric patients aged between 10-15; diagnosed as Susac syndrome. They all had thalamic involvement in addition to typical callosal lesions. All of the three patients had a monophasic course and good treatment response.